The analysis of inquiry-based learning needs at the Radya Pustaka Museum for strengthening historical literacy among secondary school students - Dewanti, Tyasanti Kusumo; Rabbani , Arsyananda (Journal on Smart Learning Technologies, 2025)
This study explores the role of inquiry-based learning (IBL) in enhancing historical literacy among secondary school students at the Radya Pustaka Museum. Historical literacy is a critical aspect of secondary education, as it equips students with the analytical skills needed to understand the complexities of historical events and their impact on contemporary society. However, traditional history education often relies on passive learning, focusing primarily on memorization rather than critical engagement with historical narratives. This study identifies key learning needs of students, such as the need for greater engagement with historical content, the development of critical thinking, research skills, and historical empathy. The research emphasizes the potential of inquiry-based learning, which encourages students to actively explore, question, and analyze historical sources, as a means of fostering deeper understanding and critical thinking. The Radya Pustaka Museum provides a unique opportunity for implementing inquiry-based learning, as it offers a wealth of primary sources and artifacts that can facilitate active, hands-on learning. This study examines the benefits of integrating IBL into the museum context, highlighting the museum’s role in helping students develop critical research skills, engage with historical material, and foster historical empathy. It also addresses the challenges of implementing inquiry-based learning, such as time constraints, teacher training, and curriculum integration. Despite these challenges, the study demonstrates that inquiry-based learning in the museum setting can significantly enhance students’ historical literacy, providing a more dynamic and engaging approach to history education. The findings suggest that inquiry-based learning, when effectively integrated into museum education, can improve historical literacy and help students become more informed, critical, and empathetic individuals.